Investigation of Social Appearance Concerns of University Students - Fatih Kırkbir; Samet Zengin (Journal of Educational Issues, 2024)
Social appearance concern is very important situation for all people’s life. Recently, this situation has revealed similar situations among university students. People exist in a social environment from people’s existence. For the fact that, people make an effort to impose themselves in their social environment and it is inevitable that the situation will cause anxiety. From this point of the view, in this study, the social appearance anxiety of the students studying at Karadeniz Technical University was investigated according to some variables. In this direction, a total of 176 students, 73 females and 103 males, from Karadeniz Technical University participated in the study. The Social Appearance Anxiety scale developed by Doğan (2010) was applied to the students participating in the study. The study is a descriptive and the -test one-way analysis of variance and correlation tests were used. According to the results of the findings obtained in the research, it was determined that the participants had a low level of social appearance anxiety. Besides, it was determined that difference between gender and class were significant. On the other hand, there were any significant difference was found in other variables.